Exploring Market Segmentation and Digital Strategies in Morocco: A Path to Competitive Advantage using big data and artificial intelligence tools. - NAOUI , Fouad; AIT ABOULEHCEN , Mouhssine (Revue Internationale du Chercheur, 2024)
Our two-part, essentially qualitative study began with an exploratory survey via an online questionnaire, generating 100 profiles, of which around ten were selected for a more in-depth main analysis using semi-structured interviews. We studied market segmentation and targeting strategies in Morocco, focusing on traditional marketing, predictive marketing, digital presence, Big Data and artificial intelligence. Traditional marketing focuses primarily on the offline interaction between the company and the consumer, while predictive marketing makes extensive use of digital presence and Big Data to gain an in-depth understanding of consumer needs, enabling the company to position itself in niche markets. Our model illustrates the interactions between digital presence, the use of Big Data, the ability to respond to consumer needs, and the application of Artificial Intelligence. We found that 80% of companies were not exploiting Big Data and that only 40% had adopted a strategic approach based on digital. What's more, 20% of companies were positioning themselves as ‘niche’ players. In our view, these companies gain a competitive advantage by using artificial intelligence to innovate and deliver unique, personalised offers to consumers in real time, outperforming the competition and driving customer satisfaction and loyalty.